Prediction of Need for Surgery After Endoscopic Balloon Dilation of Ileocolic Anastomotic Stricture in Patients With Crohn's Disease. Issue 4 (April 2015) - Lian, Lei; Stocchi, Luca; Shen, Bo; Liu, Xiaobo; Ma, Jessica; Zhang, Brook; Remzi, Feza
<x xml:space="preserve">Abstract</x> BACKGROUND: Endoscopic balloon dilation is used to treat ileocolic anastomotic stricture attributed to recurrent Crohn's disease. OBJECTIVE: The purpose of this work was to investigate long-term outcomes after dilation of ileocolic anastomotic stricture and to identify risk factors associated with the need for subsequent surgical intervention. DESIGN: This was a retrospective study based on chart review of an electronic medical chart system. SETTINGS: The study was conducted at a tertiary care center. PATIENTS: All of the eligible patients with ileocolic anastomotic stricture attributed to recurrent Crohn's disease treated with endoscopic dilation between December 1998 and May 2013 were evaluated. Patients with concurrent enterocutaneous fistula or abdominal or pelvic abscess were excluded. MAIN OUTCOME MEASURES: The main outcome measure was the need for subsequent salvage surgery because of stricture-related symptoms. RESULTS: A total of 185 patients with Crohn's disease (45.9% women; mean age, 43.1 years; symptomatic strictures in 80%) underwent 462 endoscopic dilations of ileocolic anastomosis (median per-patient dilations, 2; range, 1–3). During a mean follow-up of 3.9 years, 27 patients (14.6%) required hospitalization without surgery for stricture-related symptoms, and 66 patients (35.7%) required subsequent salvage surgery. Specific medical management, type of anastomosis, and endoscopic intralesional steroid injection had no impact on the risk of needing surgery. Significant factors associated with the need for surgery on multivariable analysis were symptomatic disease (HR, 3.54 [95% CI, 1.41–8.93]), longer time interval from last surgery (HR, 1.05 [95% CI, 1.01–1.10]), and radiographic proximal bowel dilation (HR, 2.36 [95% CI, 1.38–4.03]). A nomogram estimating the need for surgery was created with a concordance index of 0.67. LIMITATIONS: The study was limited by its retrospective design. CONCLUSIONS: Although endoscopic dilation is a valid option for ileocolic anastomotic stricture attributed to recurrent Crohn's disease, the need for surgery is common. The nomogram can identify patients who might benefit from upfront surgery.